Plantinga-Warrant and Reliabilist Warrant - Jerome Gellman (Principia: An International Journal of Epistemology)
I argue that reliabilist warrant should not require that a true belief have been produced in accordance with a design plan. At least sometimes, it seems sufficient that there be an intent for the faculty to have the reliable outcomes it in fact has. This pertains to the notion of warrant of Alvin Plantinga.